Maintenance dredging: allowable limit for dredge volume differences using SBES and MBES datasets / Raiz Razali - Razali, Raiz (2017)
In order to ensure channel clearances based on final dredging level are valid, sounding works are required to be used. The dredge volume being excavated is computed using sounding datasets. Although multi-beam echo sounders (MBES) are widely used today because of high-density data, single-beam echo sounders (SBES) are still relevant to be used to calculate dredge volume up to this date. As different hardware generates different data trends and distributions, different software uses various algorithms to calculate dredge volume and also due to different gridding sizes, it can be expected that the results with varying amounts of dredge volume will be generated. However, there is no thorough study on the magnitude of differences in dredge volume that can be established as an allowable limit. Although there are standards that can be used as a guideline, the applicable allowable limit is rarely discussed. This study aims to establish the allowable limit between SBES and MBES in terms of dredge volume calculation. Dredge volume calculation by various methods using different software, which are surface to datum, surface to surface and cross sections generated from SBES and MBES raw dataset, were compared. Five spatial interpolation methods which are inverse distance weighted (IDW), global polynomial interpolation, local interpolation polynomial, radial basis function (RBF), and ordinary kriging were used to grid the area before performing dredge volume computations. The comparative study of dredge volume differences were analyzed to justify the numerical limits in terms of total volumes generated by variable grid sizes, data distributions, cross sections, software, and spatial interpolations based on statistical analysis. The standard deviation result shows that using the allowable level of different limits, the percentage of dredge volume generated in between ± 0.5 to ± 1%.